Hyporheic exchange due to in-stream geomorphic structures. Issue 1 (31st December 2022) - Feng, Jinghong; Liu, Defu; Liu, Ying; Li, Yi; Li, Han; Chen, Lihui; Xiao, Jingwen; Liu, Jixin; Dong, Jiawei
Abstract: In-stream structures, such as channel spanning logs and weirs, can enhance hyporheic exchange in streams. Hyporheic exchange is important for stream ecosystem function, and restoring this function is a goal of many stream restoration projects. However, studies on the connection between in-stream structure size, hydrogeologic setting, and hyporheic exchange remain inadequately characterized. In this study, we combined flume experiments and numerical simulations to systematically evaluate how in-stream structure and its hydrogeologic setting impacted the hyporheic vertical exchange flux, Q, the solute penetration depth, Dp, and the solute flux, QS, in the hyporheic zone. The results showed that stream water downwells into the riverbed upstream of the weir and upwells downstream. Exchange rates were greatest near the weir and decay with distance upstream and downstream. Model results indicated Q, Dp and QS had a positive exponential relationship with the weir height, h, the flow velocity, u, and the sediment intrinsic permeability, k . While model results indicated that u was the most important factor determining Q, Dp and QS, followed by h, while only h reached a certain value, the hyporheic exchange would increase with the height and vice versa. Hyporheic exchange generally was sensitive to changes in k, only the magnitude of k varied from 10 −8 –10 −10 m 2 . This finding suggests that a rethinking of the currently applied restoration techniques is required to better consider in-stream structure size, hydrological conditions and natural substratum dynamics in river restoration.